THE CRISIS OF REPRESENTATION IN SPAIN AND THE DEFICITS OF POLITICAL PARTICIPATION: THE LIMITED SCOPE OF THE REFERENDUM/LA CRISIS DE LA REPRESENTACION EN ESPANA Y LOS DEFICITS DE PARTICIPACION POLITICA: EL LIMITADO ALCANCE DE LA INSTITUCION REFERENDARIA - i Martin, Joan Ridao (Quaestio iuris, 2015)
The current political and social debate about improving the quality of democracy has brought about a widespread questioning of the role of the so-called 'active citizenship' and the proposal of new forms of political participation beyond political parties and electoral democracy. Thus, it can be said that today, the decisive point of the concept of democracy is the right weight forms of representative democracy and direct democracy mechanisms like the referendum. Against this evidence, in Spain persists refractory attitude of political elites and part of constitutionalism, based on the memory of the key manipulation in this mode plebiscitary consultation during tardofranquismo, which has helped to maintain a constitutional and legal regulation very restrictive. In recent years, the approach to regional level consultations, decisions related to the < > of the Basque Country and Catalonia has sparked intense political debate and legal respect.Keywords: Direct democracy, representative democracy, referendum, consultive referendum, popular consultation, right to decide.El actual debate politico y social acerca de la mejora de la calidad democratica ha traido consigo un amplio cuestionamiento del rol de la denominada <<ciudadania activa>> y la propuesta de nuevas formas de participacion politica mas alla de los partidos politicos y la democracia electoral. Asi, puede decirse que hoy en dia lo que resulta determinante del concepto de democracia es la adecuada ponderacion de formas de democracia representativa y mecanismos de democracia directa como el referendum. Contra esta evidencia, en Espana persiste la actitud refractaria de las elites politicas y de parte del constitucionalismo, en base al recuerdo de la instrumentalizacion en clave plebiscitaria de esta modalidad de consulta durante el tardofranquismo, lo que ha contribuido a mantener una regulacion constitucional y legal muy restrictiva. En los ultimos anos, el planteamiento de consultas de ambito autonomico, vinculadas a decisiones sobre la < > del Pais Vasco o Cataluna, ha suscitado un intenso debate politico y juridico al respeto.Palabras clave: Democracia directa, democracia representativa, referendum, referendum consultivo, consultas populares, derecho a decidir.